OPTIMALISASI ETIKA DIGITAL PADA ANAK USIA DINI MELALUI LITERASI DIGITAL: MENDUKUNG PEMBENTUKAN KARAKTER UNGGUL DI ERA TEKNOLOGI - Asnal Mala (Atthiflah: Journal of Early Childhood Islamic Education, 2022)
The current Information Era has witnessed technological advancements that ease societal life, yet the lack of literacy culture results in a decline of insight and knowledge. Insufficient early-stage literacy education causes children to lose interest in reading and writing. The importance of instilling literacy from an early age becomes evident when children enter the Golden Age, a phase of rapid growth and development that shapes lifelong habits. The family plays a pivotal role as the primary environment in a child's life. The family's influence is critical in fostering a child's personality development and nurturing a culture of literacy within the home.The aim of this research is to explore the concept of strengthening the role of the family in fostering literacy in children. The study employed a librarian research approach, and data analysis was carried out using content analysis techniques. The research findings emphasize the significance of literacy as a vital component in a child's personal development. In the context of early childhood literacy culture, it encompasses not only reading and writing, but also active listening, critical and logical thinking, and the development of oral language intelligence. To cultivate an appreciation for literacy from an early age, parents can establish mini libraries at home and read storybooks to their children. The active involvement of parents is crucial in cultivating literacy habits among young children